Alteration of retinal rod outer segment membrane fluidity in a rat model of Smith-Lemli-Opitz syndrome - Boesze-Battaglia, Kathleen (American Society for Biochemistry and Molecular Biology, 2008)
Smith-Lemli-Opitz syndrome (SLOS) is caused by an inherited defect in the last step in cholesterol (Chol) biosynthesis, leading to abnormal accumulation of 7-dehydrocholesterol and decreased Chol levels. Progressive retinal degeneration occurs in an animal model of SLOS, induced by treating rats with AY9944, a selective inhibitor of the enzyme affected in SLOS. Here we evaluated alterations in the biochemical and physical properties of retinal rod outer segment (ROS) membranes in this animal model. At 1 month of AY9944 treatment, there were modest alterations in fatty acid composition, but no significant differences in cis-parinaric acid (cPA) spectroscopic parameters in ROS membranes from treated versus control rats. However, at 3 months, ROS docosahexaenoic acid (DHA) content was dramatically reduced, and cPA fluorescence anisotropy values were decreased, relative to controls. Also, 1,6-diphenyl-1,3,5-hexatriene exhibited decreased rotational motion and increased orientational order in ROS membranes from 3 month-old AY9944-treated rats, relative to controls. No significant changes in protein:lipid ratios were observed; however, rhodopsin regenerability was compromised by 3 months of treatment. These findings are consistent with reduced ROS membrane fluidity in the SLOS rat model, relative to controls, primarily due to the dramatic reduction in membrane DHA levels, rather than altered sterol composition.